2020
DOI: 10.1021/acs.biomac.0c01077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stereochemistry and Hydrogen Bonding on Glycopolymer–Amyloid-β Interactions

Abstract: Detailed description of synthesis and isolation of S2 polymers, HMBC NMR and HSQC NMR spectra of small-molecule analogues, stacked 1 H NMR spectra of glycopolymers with small-molecule analogues, stacked variable temperature NMR spectra of glycopolymers and small-molecule analogues, and temperature coefficient plots of hydroXyl proton shifts for glycopolymers and small-molecule analogues (PDF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 69 publications
(95 reference statements)
0
16
0
Order By: Relevance
“…Nevertheless, it is evident that GM1 ganglioside enrichment promotes oligomers vis-à-vis membrane disruption as opposed to unenriched liposomes. To specifically see whether glycoform distributions on the gangliosides have an effect on these properties, as we had seen before with Aβ-glycopolymer interactions 43,44 , TBE liposomes were also enriched with GM3 gangliosides which have significant sugar distribution differences with GM1 (Figure S2). By doing so, none or minimal leakage of dye upon incubation of Aβ monomers with 50% GM3 enriched TBE LUVs (; Figure 4e) was observed.…”
Section: Resultsmentioning
confidence: 87%
“…Nevertheless, it is evident that GM1 ganglioside enrichment promotes oligomers vis-à-vis membrane disruption as opposed to unenriched liposomes. To specifically see whether glycoform distributions on the gangliosides have an effect on these properties, as we had seen before with Aβ-glycopolymer interactions 43,44 , TBE liposomes were also enriched with GM3 gangliosides which have significant sugar distribution differences with GM1 (Figure S2). By doing so, none or minimal leakage of dye upon incubation of Aβ monomers with 50% GM3 enriched TBE LUVs (; Figure 4e) was observed.…”
Section: Resultsmentioning
confidence: 87%
“…Helical wrapping of SWCNTs by natural polysaccharides and synthetic glycopolymers is an effective approach to preserve nanotube properties while stabilizing tubes in an aqueous environment ( Star et al, 2002 ; Hasegawa et al, 2004 ; Dohi et al, 2006 ; Cantwell et al, 2020 ). In addition to van der Waals attractions and hydrophobic interactions between the hydrophobic faces of the pyranose rings and the hydrophobic surface of nanotubes, intra- and inter-molecular hydrogen bonds of carbohydrates with neighboring sugar units and water molecules further stabilize the helical conformation of polymers on the surface of nanotubes ( Çarçabal et al, 2005 ; Bristol et al, 2020 ; Liu et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the relatively weak interactions between monomeric saccharide and CBPs featuring hydrogen bonding and chelation with ions, biological systems employ a saccharide-assembly structure of oligosaccharides to amplify carbohydrate-protein interactions ( Zhang et al, 2010 ; Cecioni et al, 2015 ; Bernardi et al, 2013 ). Therefore, developing biomimetic synthetic materials that feature multivalent carbohydrate-protein interactions has vast potential in biomedical applications, including biosensing, drug delivery, therapeutics, and pathogen inhibition ( Zhang et al, 2010 ; Richards et al, 2012 ; Miura et al, 2016 ; Bristol et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The blue surfaces of the P0A223 indicates that the interpolated charge of the entire P0A223 is higher than that of P0A223. In general, the interpolated charge surface are often used to determine hydrogen bonding patterns, electrostatic interaction and strengths of salt bridges in biomolecular simulations 59 . Many studies have also confirmed that amino acids with charged side chains could be regarded as the important factor for the increase of the thermostability of proteins 35 , 57 where positively and negatively charged amino acids contain (Arg, His and Lys) and (Asp and Glu), respectively.…”
Section: Resultsmentioning
confidence: 99%